Barnum Effect pada Kepribadian Lima Faktor - Andi Tenri Faradiba; Ni Made Rai Kistyanti; Fahira Maulidina; Riska Indriani (Jurnal Ilmiah Psikologi MIND SET, 2021)
The Barnum Effect is the tendency of individuals to accept personality feedback as true information, regardless of its validity. In this case, personality is defined as a relatively settled pattern that individuals have and use to adapt to their environment. The factor approach is used in defining personality which consists of five personality factors, namely openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. This study aims to test whether there is a Barnum Effect on personality in the adolescent population. The research design used is experimental and the type of research is one group pre-posttest. There were 138 students who were given manipulation in the form of a fake personality test and asked questions about the accuracy of their personality test results. The data in this study indicate that there are differences in personality scores on the factors of neuroticism, openness to experience, and agreeableness before being given personality feedback and after being given feedback. That is, there is a Barnum Effect found in adolescents and personality feedback has an effect on how adolescents perceive their personality.